2008
DOI: 10.1007/bf03175564
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of marine associated bacteria from Tamil Nadu, Southeast coast of India for potential antibacterial activity

Abstract: The bacteria associated with living surfaces are rich sources of bioactive metabolites. In the present study, 182 heterotrophic epibacterial colonies, isolated from seaweeds (44%), ascidians (30.2%), barnacles (10.4%) and molluscan egg mass (15.4%), were subjected to high throughput screening by cross streaking method against six human pathogenic bacteria, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Vibrio cholerae, Proteus mirabilis and Klebsiella pneumoniae. The 137 epibacterial isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The secondary metabolites produced by these bacteria are highly recognized for their importance in the field of biomedical applications ( Armstrong et al, 2001 ; Kelecom, 2002 ; Burgess et al, 2003 ). Antimicrobial activity of the epiphytic bacterial communities from seaweeds have been reported ( Kanagasabhapathy et al, 2006 , 2008 ; Vijayalakshmi et al, 2008 ; Ravisankar et al, 2013 ; Horta et al, 2014 ; Martin et al, 2014 ; Karthick et al, 2015a ), similarly anti-diatom activity have also been observed by Kumar et al (2011) . In the Andaman Islands, luxuriant growth of all the three groups of seaweeds are available throughout the year.…”
Section: Introductionmentioning
confidence: 93%
“…The secondary metabolites produced by these bacteria are highly recognized for their importance in the field of biomedical applications ( Armstrong et al, 2001 ; Kelecom, 2002 ; Burgess et al, 2003 ). Antimicrobial activity of the epiphytic bacterial communities from seaweeds have been reported ( Kanagasabhapathy et al, 2006 , 2008 ; Vijayalakshmi et al, 2008 ; Ravisankar et al, 2013 ; Horta et al, 2014 ; Martin et al, 2014 ; Karthick et al, 2015a ), similarly anti-diatom activity have also been observed by Kumar et al (2011) . In the Andaman Islands, luxuriant growth of all the three groups of seaweeds are available throughout the year.…”
Section: Introductionmentioning
confidence: 93%
“…The prepared discs were placed on the inoculated plates and the plates were incubated at 37 o C for 24 hours. After incubation, the zone of inhibition was measured from border of the disc to the edge of the clear zone (Vijayalakshmi et al, 2008).…”
Section: Disc Diffusion Assay Methodsmentioning
confidence: 99%